Research on the experience and lessons of ethnic and religious governance in the EU under the rise of populism - you, nan (Pacific International Journal, 2024)
As a community of multicultural and religions, the effective governance of ethnic and religious affairs is of great significance for maintaining the stability within the EU and promoting the harmony and cooperation among member states. The EU has strengthened ethnic and religious governance by promoting multicultural policies, implementing regional policies, establishing conflict prevention and mediation mechanisms, promoting cross-border cooperation and integration process, focusing on protecting the rights and freedom of citizens, establishing a legal and policy framework, and strengthening dialogue. However, under the rise of populism, the EU is severely challenged, including the intensification of immigration and refugee problems, the insufficient response to religious extremism and terrorist threats and the lack of coherence and consistency of policies, the lack of effective communication and dialogue mechanisms, and insufficient regulation.The article suggests vigilance the dangers of populism, strengthening the rule of law, focusing on education and publicity, preventing and responding to extremism, and promoting the integration of economic development and society. The EU has taken measures, such as promoting legal policy making, strengthening dialogue mechanisms and the governance of migrants, but it still needs to focus on social integration to maintain stability and solidarity. Other countries can learn from the EU experience and develop religious governance strategies adapted to their own situation.